Efeito imunomodulatório do receptor CLEC7A no reconhecimento imune inato de Neospora Caninum - Silva, Murilo Vieira da (2013)
A major cause of abortion in cattle is due to infection with Neospora caninum. Several pattern recognition receptors have been studied in the immune response against infection by this protozoan which has extensive suface protein glycosylation. Thus, this work aimed to evaluate the role of the innate immune receptor C-type lectin (CLEC7A), a binder of glycans, during N. caninum infection. It was observed through of experimental infections in wild type (WT) and CLEC7A deficient (CLEC7A-/-) C57BL/6 mice, that the absence of this receptor induces increased survival, lower acute and chronic parasitism, and increase of the proinflammatory cytokines production. It was also noted lower parasitism in Bone Marrow Derived Macrophages (BMDMs) infected with N. caninum. Additionally, it was found that both BMDMs as Dendritic Cells Derived from Bone Marrow (BMDCs) CLEC7A-/- showed increased production of IL-1β, IL-6, IL-12p40, TNFa and IL-10. Due to CLEC7A immunomodulatory function, it s used Laminarin to block this receptor in protocol of the immunization and treating against protozoan infection in question. It was observed that Laminarin administration induces the higher ROS and IL-12p40 production by peritoneal cells, reduces the acute and chronic parasitism and therefore chronic cerebral inflammation. In addition, Laminarin-treatment reduced IgG1 production and increased antigen-recognition by antibodies. During Laminarin administration in vitro assays, it was observed lower parasitism in BMDMs treated with the blocker and the absence of cytotoxic activity of this. The results demonstrate that CLEC7A is involved in the immune response to N. caninum infection and this parasite use the receptor to modulate the immune response. Therefore CLEC7A blockers like Laminarin can be applied to prophylactic and therapeutic protocols against infection by the parasite.